Pengaruh Kompetensi, Kompensasi dan Komunikasi terhadap Kinerja Pegawai pada Dinas Kebudayaan dan Pariwisata Provinsi Sumatera Utara - Putri, Jeni Aina; Sari, Ade Indah; Setiawan, Teguh (Jurnal PKM Manajemen Bisnis, 2024)
Human resources are critical to a company's success as they impact objectives. Developing this activity demands management. Developing these activities demands management. Companies help related groups develop in various ways. Agency performance is largely influenced by employees. This study aims to examine how competence, compensation, and communication affect employee performance at the Office of Culture and Tourism of North Sumatra Province. This primary data analysis uses employee performance as the independent variable and competence, compensation, and communication as the dependent variable. This research involved employees of the Culture and Tourism Office of North Sumatra Province. Quantitative associative research was used. A saturated sample of 125 respondents was used in this study. This study collected data with a questionnaire. This study uses SPSS to conduct data quality tests (Validity and Reliability), classical assumption tests, and hypothesis testing (Test f, Test t, Test Coefficient of Determination).The results of this study indicate that the competency variable has a significant effect on employee performance with the results obtained from the tcount value of t table 2. 536> t table 1,984 with a significance level of 0.000 <0.05, the compensation variable has a significant effect on employee performance with the results obtained by the tcount value of 10,428> t table 1,984 with a significance value of 0.000 <0.05, the communication variable has a significant effect on employee performance with the results obtained by the tcount value of 1,990> t table 1,984 with a significance value of 0.000 <0.05.